Fiscal Asymmetric Decentralization and the Influence of County Fiscal Autonomy on Household Effects in Kenya - Cyrus Mwangi Munyua; Stephen Muchina; Beatrice Ombaka (Integrated Journal of Business and Economics (IJBE), 2020)
Fiscal asymmetric decentralization is seen as the panacea in solving persistent income inequalities facing developing economies. Despite efforts to finance County governments, about 42% of Kenyan’s 47.6 million people still live below the poverty level. This study evaluates the influence of County fiscal autonomy on household effects in Kenya. Both primary and secondary data, collected from households in 47 county governments and the Commission on Revenue Allocation, respectively. A Sample of 4,813 households was drawn from 96,251 lists of households developed by Kenya National Bureau of Statistics. Cochran's correction formula was used. The result finds an insignificant negative correlation between county fiscal autonomy and household effects in Kenya. Further studies are recommended with diverse indicators. Findings in this paper are generalizable and a point of reference for policymakers in Kenya.